Energy Balances and Greenhouse Gas Emissions of Agriculture in the Shihezi Oasis of China - Zhengang Yan (Atmosphere, 2020)
The objective of this study was to evaluate the difference of crop and livestock products regarding energy balances, greenhouse gas (GHG) emissions, carbon economic efficiency, and water use efficiency using a life cycle assessment (LCA) methodology on farms in three sub-oases within the Shihezi Oasis of China. The three sub-oases were selected within the Gobi Desert, at Shizongchang (SZC), Xiayedi (XYD), and Mosuowan (MSW), to represent the various local oasis types: i. Oasis; ii. overlapping oasis-desert; and iii. Gobi oasis. The results indicated that crop production in XYD Oasis had higher energy balances (221.47 GJ/ha), and a net energy ratio (5.39), than in the other two oases (p < 0.01). The production of 1 kg CW of sheep in XYD Oasis resulted in significantly higher energy balances (18.31 MJ/kg CW), and an energy ratio (2.21), than in the other two oases (p < 0.01). The water use efficiency of crop production in the SZC Oasis was lower than that of the XYD and MSW oases (p < 0.05). Alfalfa production generated the lowest CO2-eq emissions (8.09 Mg CO2-eq/ha. year) and had the highest water use efficiency (45.82 MJ/m3). Alfalfa (1.18 ¥/kg CO2-eq) and maize (1.14 ¥/kg CO2-eq) had a higher carbon economic efficiency than other crops (p < 0.01). The main sources of GHG emissions for crop production were fertilizer and irrigation. The structural equation modelling (SEM) of agricultural systems in the Shihezi Oasis showed that the livestock category significantly influenced the economic income, energy, and carbon balances.